TRENDS AND PROBLEMS OF BUDGET INVESTMENTS DEVELOPMENT - T. Shhukina (Вестник университета)
There are some problems which hinder the development of budget investment in the public sector. Inecient using of budget funds, limited liability for inappropriate or ineective using of budget funds, poor elaboration of the organization of budget planning and execution of budgets, high level of corruption, insucient monitoring of the implementation of infrastructure projects are considered in the article. Digital materiaes on the implemented investment programs for the period 2013-2017 is given, and this allows to trace the dynamics of the studied issue.